1984
DOI: 10.1093/infdis/150.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Hepatitis B in Tennessee Prisoners

Abstract: A prevalence serosurvey was performed on an 11.7% sample of the 6,503 adult male inmates in Tennessee prisons. On the basis of the sample, 0.9% of the prisoners possessed hepatitis B surface antigen, and 29.5% had one or more serum markers for hepatitis B virus (HBV). Thirty-two possible risk factors were analyzed for association with possession of HBV serum markers. The significant risk factors for possession of HBV markers in this population were found to be age, intravenous drug use while not incarcerated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 18 publications
2
47
3
4
Order By: Relevance
“…Even before the AIDS epidemic, surveys across facilities indicated that 25-40% of male inmates entering prison had a history of injection drug use, [7][8][9] which is substantially higher than the estimate of 0.6% for the general population. 10 Surveys also estimated that up to 7% of males entering prison were homosexual, 7 but this estimate was not very different for estimates generated for the general population.…”
Section: Prison Entry Risk Behaviors Of Inmates Entering Prisonmentioning
confidence: 80%
See 1 more Smart Citation
“…Even before the AIDS epidemic, surveys across facilities indicated that 25-40% of male inmates entering prison had a history of injection drug use, [7][8][9] which is substantially higher than the estimate of 0.6% for the general population. 10 Surveys also estimated that up to 7% of males entering prison were homosexual, 7 but this estimate was not very different for estimates generated for the general population.…”
Section: Prison Entry Risk Behaviors Of Inmates Entering Prisonmentioning
confidence: 80%
“…10 Surveys also estimated that up to 7% of males entering prison were homosexual, 7 but this estimate was not very different for estimates generated for the general population. 11 Thus, injection drug use prior to incarceration was thought to account for a substantial proportion of the HIV infection among prison inmates.…”
Section: Prison Entry Risk Behaviors Of Inmates Entering Prisonmentioning
confidence: 99%
“…A prevalência da infecção pelo vírus da Hepatite B (VHB) tem sido descrita através do rastreamento sorológico de grupos populacionais selecionados como doadores de sangue 10 , gestantes 12 , grupos de risco, incluindo homossexuais masculinos 37,41 , hemodialisados 17 , usuários de drogas endovenosas 11 , presidiários 14 , profissionais da área de saúde 15,36 e militares 25 . A primeira vista, o rastreamento sorológico de doadores de sangue parece ser uma situação privilegiada para estudos de prevalência da infecção pelo VHB, pois grande contingente de indivíduos são submetidos a triagem laboratorial de rotina, consti- tuindo-se em grupo populacional de fácil acesso e a baixo custo operacional.…”
Section: Introductionunclassified
“…In our sample, a total of 424,291 people were admitted annually, representing 69% of the 615,226 annual admissions to state or federal prisons. 25 Of all inmates in custody of their state Department of Correction, 2.1%, or 22,204 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20] The seroprevalence of markers for HBV infection within incarcerated populations is high, ranging from about 16% to 50%. 12,13,[21][22][23] The risk of intra-prison transmission is highlighted by a recent outbreak of hepatitis B within a state correctional facility. Serological testing for acute hepatitis B in that entire facility revealed an incidence of 1.2% per six months, and that investigation is ongoing.…”
Section: Synopsismentioning
confidence: 99%